(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the analgesic effectiveness and identify side effects over time of continuous epidural anesthesia (CEA) during labor. Research Method: A prospective observational study conducted on 115 women undergoing vaginal delivery at Hai Phong Obstetrics Hospital from January to April 2026. The women received continuous analgesia with a syringe pump delivering a mixture of 0.1% Levobupivacaine and 2 mcg/ml Fentanyl. Pain scores using VAS were assessed at four time points: before anesthesia, 30 minutes after anesthesia, at delivery, and during perineal suturing; side effects were monitored during labor and up to 48 hours postpartum. Results: Regarding pain relief, the average VAS score significantly decreased from 8.2 (before CEA) to 3.4 at 30 minutes post-anesthesia; at delivery, the VAS increased to 6.9 due to mechanical pressure in the pelvic area; then decreased to 2.5 during perineal suturing. Concerning side effects, during labor, the most common symptoms were chills (32.2%), leg numbness (22.6%), back pain (20%), and nausea (18.2%). However, after 48 hours, most of these symptoms disappeared or significantly decreased, with the low back pain rate reduced to only 9.5% and no serious complications observed.